2020
DOI: 10.1161/circinterventions.119.008963
|View full text |Cite
|
Sign up to set email alerts
|

Munich Comparative Study

Abstract: Background: Percutaneous pulmonary valve implantation (PPVI) has become an important treatment of right ventricular outflow tract dysfunction. Studies directly comparing the long-term outcome of PPVI with the Melody valve to surgical pulmonary valve replacement (SPVR) are lacking. Methods: All patients treated with PPVI with the Melody valve and SPVR between January 2006 and December 2018 in our center were enrolled into a database and investigated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 18 publications
1
23
0
3
Order By: Relevance
“…As a result, only one case of type 1 fracture was observed. The efforts made to prevent and reduce the occurrence of fractures of hemodynamically important valves are likely to yield even better long-term outcomes than those documented in previous studies [ 5 , 6 , 7 , 32 ].…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…As a result, only one case of type 1 fracture was observed. The efforts made to prevent and reduce the occurrence of fractures of hemodynamically important valves are likely to yield even better long-term outcomes than those documented in previous studies [ 5 , 6 , 7 , 32 ].…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, several noteworthy changes in implantation practices and outcomes have been observed over time that likely reflect the learning curve effects, protocol modifications, and an evolving understanding of better practices [ 25 , 26 , 27 , 28 ]. Previously, patients were more likely to undergo PPVI with the smallest delivery systems (18 mm), which resulted in a high residual pressure gradient across the RVOT and more frequent stent fractures and reinterventions [ 6 , 7 ]. Furthermore, in 2007, Nordmeyer et al reported a 21.1% (26 of 123) incidence rate of stent fractures after PPVI, which is main cause of TPV dysfunction and has become less common since pre-stenting became more widely implemented [ 18 , 25 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Die Beurteilung der Interventionsergebnisse wird durch einige Faktoren erschwert: Die Implantationszahlen sind im Vergleich zum Aortenklappenersatz deutlich geringer und die behandelten Patientengruppen sehr inhomogen. Sie unterscheiden sich beträchtlich im Alter, in den Diagnosen, in der chirurgischen Therapie und in der Pathophysiologie (Stenose, Insuffizienz, gemischtes Vitium) [1,5].…”
Section: Langzeitergebnisseunclassified